Forms and functions of human SDR enzymes. - Oppermann, U; Filling, C; Jörnvall, H (2001)
Short-chain dehydrogenases/reductases (SDR) are defined by distinct, common sequence motifs but constitute a functionally heterogenous superfamily of enzymes. At present, well over 1600 members from all forms of life are annotated in databases. Using the defined sequence motifs as queries, 37 distinct human members of the SDR family can be retrieved. The functional assignments of these forms fall minimally into three main groups, enzymes involved in intermediary metabolism, enzymes participating in lipid hormone and mediator metabolism, and open reading frames (ORFs) of yet undeciphered function. This overview, prepared just before completion of the human genome project, gives the different human SDR forms and relates them to human diseases.